Effects of intratumoral microbiota on tumorigenesis, anti-tumor immunity, and microbe-based cancer therapy - Zheng, Jingwei (Frontiers in Oncology, 2024)
Intratumoral microbiota (IM) has emerged as a significant component of the previously thought sterile tumor microenvironment (TME), exerting diverse functions in tumorigenesis and immune modulation. This review outlines the historical background, classification, and diversity of IM, elucidating its pivotal roles in oncogenicity, cancer development, and progression, alongside its influence on anti-tumor immunity. The signaling pathways through which IM impacts tumorigenesis and immunity, including reactive oxygen species (ROS), β-catenin, stimulator of interferon genes (STING), and other pathways [NF-κB, Toll-like receptor (TLR), complement, RhoA/ROCK, PKR-like ER kinase (PERK)], are discussed comprehensively. Furthermore, we briefly introduce the clinical implications of IM, emphasizing its potential as a target for novel cancer therapies, diagnostic biomarkers, and prognostic indicators. Notably, microbe-based therapeutic strategies such as fecal microbiome transplantation (FMT), probiotics regulation, bacteriotherapy, bacteriophage therapy, and oncolytic virotherapy are highlighted. These strategies hold promise for enhancing the efficacy of current cancer treatments and warrant further exploration in clinical settings.